The effects of beach nourishment on benthic invertebrates in eastern Australia: Impacts and variable recovery - Schlacher, T; Noriega, R; Jones, A; Dye, T (Science of The Total Environment, 2012)
Beach erosion is likely to accelerate, driven by predicted consequences of climate change and coastal development. Erosion is increasingly combated by beach nourishment, adding sand to eroding shores. Because a range of engineering techniques exists to nourish beaches, and because these techniques differ in their environmental effects, assessments of ecological impacts need to be tailored and specific. Here we report on impacts and recovery of benthic invertebrates impacted by beach nourishment operations undertaken at Palm Beach (SE Queensland, Australia). Assessments are made based on a beyond-BACI design, where samples were taken once before nourishment and twice afterwards at the impact and two control sites. Because almost all of the sand was deposited on the upper beach and later moved with bulldozers down-shore, we specifically examined whether the effects of nourishment varied at different heights of the beach—a little-studied question which has management implications. Impacts on the fauna were massive on the upper and middle levels of the beach: samples collected two days after the conclusion of nourishment were entirely devoid of all invertebrate life (‘azoic’), whereas weaker effects of nourishment were detectable on the lower shore. Recovery after five months also varied between shore levels. The sediment of the upper level near the dunes remained azoic, the fauna of the middle shore had recovered partially, and the lower level had recovered in most respects. These findings indicate that the height and position of sand placement are important. For example, rather than depositing fill sand on the intertidal beach, it could be placed in the shallow subtidal zone, followed by slow up-shore accretion driven by hydrodynamic forces. Alternatively, techniques that spread the fill sand in thin layers (to minimize mortality by burial) and leave unfilled intertidal refuge islands (to provide colonists) may minimize the ecological impacts of beach nourishment.